2020
DOI: 10.1016/j.drup.2020.100719
|View full text |Cite
|
Sign up to set email alerts
|

FDA approved drugs with pharmacotherapeutic potential for SARS-CoV-2 (COVID-19) therapy

Abstract: In December 2019, a novel SARS-CoV-2 coronavirus emerged, causing an outbreak of life-threatening pneumonia in the Hubei province, China, and has now spread worldwide, causing a pandemic. The urgent need to control the disease, combined with the lack of specific and effective treatment modalities, call for the use of FDA-approved agents that have shown efficacy against similar pathogens. Chloroquine, remdesivir, lopinavir/ritonavir or ribavirin have all been successful in inhibiting SARS-CoV-2 in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
131
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(142 citation statements)
references
References 129 publications
1
131
0
3
Order By: Relevance
“…Up to this point, HCQ has been used for the treatment of malaria or autoimmune diseases such as rheumatoid arthritis, discoid and systemic lupus erythematosus (Plaquenil Label, 2017 ; Plaquenil SmPC, 2020 ). However, HCQ seems to offer a dual beneficial action for COVID-19 patients, as it exerts both immunomodulatory and antiviral effects (Drożdżal et al., 2020 ). In fact, some recent studies have revealed the drug’s in vitro antiviral activity (Liu et al., 2020b ; PAHO/WHO, 2020 ; Yao et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to this point, HCQ has been used for the treatment of malaria or autoimmune diseases such as rheumatoid arthritis, discoid and systemic lupus erythematosus (Plaquenil Label, 2017 ; Plaquenil SmPC, 2020 ). However, HCQ seems to offer a dual beneficial action for COVID-19 patients, as it exerts both immunomodulatory and antiviral effects (Drożdżal et al., 2020 ). In fact, some recent studies have revealed the drug’s in vitro antiviral activity (Liu et al., 2020b ; PAHO/WHO, 2020 ; Yao et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering all the above and based on the reported antiviral activity of the compound (Drożdżal et al., 2020 ; Liu et al., 2020b ; Yao et al., 2020 ), there is currently a need to rationalize the administered dosing schemes in order to maximize the efficacy and safety of HCQ in patients with COVID-19. Eventually, additional time is needed in order to retrieve concrete results from new in vitro and in vivo studies specifically designed for HCQ against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first reported on December 2019 from Wuhan City, Hubei, China ( Zhu et al, 2020 ; Lu et al, 2020 ) and is currently causing major concern in the medical community, as it exhibits faster human-to-human transmission often combined with asymptomatic, or minimally symptomatic course of the infection ( Drożdżal et al, 2020 ). These two factors are perhaps the major contribution of the rapid propagation of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…The novel coronavirus, SARS-CoV-2, causing coronavirus disease 2019 (COVID-19) is a major health threat that was declared a global pandemic by the World Health Organization (WHO) in March 2020 [1][2][3]. Since the outbreak in December 2019, many people have suffered from a severe acute respiratory infection that causes respiratory failure, the need for intubation, and prolonged mechanical ventilation [4].…”
Section: Introductionmentioning
confidence: 99%